Persepsi Siswa Kelas VIII SMPN 2 Pariaman terhadap Pelaksanaan Model Direct Method Berbantuan Aplikasi FonBi dalam Pembelajaran Menyaji Teks Laporan Pengamatan - Rahma, Annisa Nurul; Nursaid, Nursaid; Detrial, Claudhea Enjelina; Suryani, Nurul; Utami, Vebby Novedra (Indonesian and Regional Language and Literature Department, Universitas Negeri Padang, 2023)
Learning Indonesian aims to enable students to achieve six language skills, one of which is presenting skills. This research aims to describe the perceptions of class VIII students at SMPN 2 Pariaman regarding the implementation of the direct method model assisted by the FonBi application in learning to present observation report texts. The type of research used in this research is quantitative research with descriptive methods. The population in this study were class VIII students at SMPN 2 Pariaman. The sample in this study was selected using a probability sampling technique, the type of purposive sampling, namely class VIII. 3 as a class that applies the direct method model assisted by the FonBi application in learning to present observation report texts. The research results show that there is a good perception of the implementation of the direct method model assisted by the FonBi application in learning to present observation report text with an average score of 76.57 with